Recommendations for the treatment of migraine attacks - a Brazilian consensus - Bordini, Carlos Alberto; Roesler, Celia; Carvalho, Deusvenir de Souza; Macedo, Djacir Dantas P.; Piovesan, Elcio; Melhado, Eliana Meire; Dach, Fabiola; Kowacs, Fernando; Silva Junior, Hilton Mariano da; Souza, Jano Alves de; Maciel, Jayme Antunes; Freitas de Carvalho, Joao Jose de; et al. (Assoc Arquivos Neuro- Psiquiatria, 2016)
In this article, a group of experts in headache management of the Brazilian Headache Society developed through a consensus strategic measurements to treat a migraine attack in both the child and the adult. Particular emphasis was laid on the treatment of migraine in women, including at pregnancy, lactation and perimenstrual period.
Keywords: headache; migraine; treatment; pain medication; crisis